The First Local Experience of Use of Extracorporeal Circulatory Support with PROTEKDuo Dual-Lumen Cannula in a Patient with Acute Right Ventricular Failure - Oleksandr M. Dovgan; Maksim E. Paulouski; Alona I. Honcharenko; Anton V. Makedon; Yevhen V. Prystaia (Ukrainian Journal of Cardiovascular Surgery, 2023)
Acute right ventricular failure is a life-threatening condition that can occur as a result of a sudden increase in total pulmonary vascular resistance, in particular, as a result of pulmonary embolism. Most patients with thromboembolism are treated with thrombolytic therapy, but in some cases open thrombextraction is preferred. Removal of blood clots from the pulmonary vascular bed and cardiopulmonary bypass can lead to spasm of the pulmonary artery and to the elevation of total pulmonary resistance, which, in turn, increases the afterload on the right ventricle and can lead to a dramatic decrease in its mechanical function.The aim. The aim of this report is to present the first experience of using the right ventricular bypass with the PROTEKDuo cannula for the purpose of temporary mechanical support of the right ventricle.Case presentation. We studied a 63-year-old patient who underwent Studer technique for bladder adenocarcinoma. On the 14th day an acute massive pulmonary embolism occurred with a drop in hemodynamics and the presence of a floating clot on the right atrium. Thrombolysis carried significant risks due to possible bleeding and clot fragmentation in the right atrium with subsequent embolization of the pulmonary arteries. In these circumstances, open thrombectomy under hypothermic arrest was performed. Intraoperatively, the patient developed acute right ventricular failure resistant to all conservative therapy, therefore, right ventricular bypass was connected using PROTEKDuo, which made it possible to overcome the phenomena of acute right ventricular failure in the postoperative period.Conclusions. Our experience with right ventricular bypass using the PROTEKDuo dual-lumen cannula demonstrates another useful option for saving patients with isolated right ventricular failure.